035 Case-control study of risk factors for stroke among critically-ill patients with SARS-CoV-2: an analysis of the COVID-19 critical care consortium (CCCC) global registry. (23rd August 2021) - Fanning, Jonathon P; Barnett, Adrian; Whitman, Glenn; Arora, Rakesh; Premraj, Lavien; Battaglini, Denise; Huth, Sam; Porto, Diego Bastos; Choi, Huimahn; Suen, Jacky; Bassi, Gianluigi Li; Fraser, John; et al.
Abstract : Objective: COVID-19 has been identified as a risk factor for severe cerebrovascular complications, albeit mostly in small patient populations, limited to specific regions, and including all severities of disease. Utilising the largest database of critically-ill COVID-19 patients, we investigated risk factors for stroke in intensive care unit (ICU) COVID-19 patients. Methods: Data for this matched case-control study were extracted from a large international registry of adult COVID-19 patients requiring ICU admission. Patients with imaging-confirmed cerebrovascular events identified following ICU admission were compared against five controls per case, matched for demographics, morphometrics, illness severity, and ICU days. Expert consensus determined key clinical and laboratory variables for risk assessment. Results: From January 1-December 21 2020, 2, 715 ICU patients were registered across >370 sites spanning 52 countries; acute stroke was identified during the ICU stay in 59(2.2%); 27(46%) haemorrhagic, 19(32%) ischaemic, 13(22%) unspecified. Stroke patients had higher SOFA and APACHE scores, more frequent hypertension and cardiovascular disease, and more often required mechanical ventilation, vasopressors, and ECMO. Diabetes, hypertension, smoking, and Caucasian ethnicity were identified as risk factors for ischaemic versus haemorrhagic stroke and being stroke-free. Ethnicity (Hispanic or black), higher PaO2, and extracorporeal membrane oxygenation (ECMO) were significant risk factors for haemorrhagic stroke.Anticoagulation had no association with either stroke subtype. Conclusions: Severe illness and more aggressive management were major risk factors for acute stroke. Traditional vascular risk factors and Caucasian ethnicity were risk factors for ischaemic stroke, while Hispanic or black ethnicity, higher PaO2, and ECMO were significant risk factors for haemorrhagic stroke.